Analisis Risiko Teknologi Informasi Aplikasi CATTER PDAM Kota Salatiga Menggunakan ISO 31000 - Enik Muryanti; Kristoko Dwi Hartomo (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2021)
Catat Meter (CATTER) is a recording system for customer water meter stands at PDAM Salatiga City. The Catat Meter application helps companies in the process of entering customer water meter stand data every day and makes it easier to report water bills for residents of the City of Salatiga. The study was conducted using the ISO 31000 method, which is a framework used as a guideline for implementing risk analysis management which has several stages, namely the first stage of risk assessment which consists of 3 stages, namely risk identification, risk analysis, risk evaluation. The next stage is risk treatment. There are 4 possible risks that are included in the high level, 13 possibilities that are included in the medium level, and 9 possible risks that are included in the low level. The problem that arises is the lack of maintenance processes on assets owned by the Catat Meter application that have not been carried out optimally. By implementing risk reduction, the company is able to minimize the possible risks and impacts.